2003
DOI: 10.1021/jp0349536
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale Ice Fluidity in NOx Photodesorption from Frozen Nitrate Solutions

Abstract: The temperature-programmed desorption of nitric oxide, NO, and nitrogen dioxide, NO 2 , during the 302 nm photolysis of KNO 3 -doped, spray-frozen ice layers was investigated using two-photon laser-induced NO x fluorescence detection in the range -35 e T/°C e 0. Upon applying steady illumination and a 0.67 °C min -1 heating ramp, frozen KNO 3 solutions begin to evolve NO 2 at increasing rates, while NO emissions plateau soon after until, at ∼ -8 °C, both species surge abruptly. Although the primary photoproduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(60 citation statements)
references
References 39 publications
0
60
0
Order By: Relevance
“…Similarly, previous studies of the NO 3 − photolysis using natural or artificial snow samples [3,5,18,21] or thin ice layers [23,26] have also indicated that the NO x flux to the gas phase was dominated by NO 2 , although in most cases the emission of NO was not negligible with ratios of the NO 2 to NO production rates between 2 and 8 in the snow experiments [5,18,21] and ratios between 10 and 23 in the experiments with the ice films [23,26]. However, the formation of NO possibly indicates further reactions in the gas phase like the photolysis of NO 2 and HONO, which can also lead to the formation of NO.…”
Section: Comparison With Field Data: No X Emissionsmentioning
confidence: 73%
See 3 more Smart Citations
“…Similarly, previous studies of the NO 3 − photolysis using natural or artificial snow samples [3,5,18,21] or thin ice layers [23,26] have also indicated that the NO x flux to the gas phase was dominated by NO 2 , although in most cases the emission of NO was not negligible with ratios of the NO 2 to NO production rates between 2 and 8 in the snow experiments [5,18,21] and ratios between 10 and 23 in the experiments with the ice films [23,26]. However, the formation of NO possibly indicates further reactions in the gas phase like the photolysis of NO 2 and HONO, which can also lead to the formation of NO.…”
Section: Comparison With Field Data: No X Emissionsmentioning
confidence: 73%
“…Several laboratory studies have provided evidence that the photolysis of nitrate and the subsequent reactions in ice and snow take place in a so-called quasi-liquid layer (QLL) on the surface of ice crystals [19,20,22,23]. Although the properties of the QLL are not well established, it is now well known that at temperatures close to the melting point and/or in the presence of impurities, the QLL shows a strongly enhanced disorder compared to the highly ordered interior of the ice crystal (e.g.…”
Section: Development Of a Reaction Mechanism For The Transformation Omentioning
confidence: 99%
See 2 more Smart Citations
“…Research into the adsorption of gaseous impurities on ice and snow has been carried out in laboratory studies by many groups ͑Clapsaddle and Lamb, 1989; Valdez et al, 1989;Mitra et al, 1990;Conklin and Bales, 1993;Chen and Crutzen, 1994;Tabazadeh et al, 1999;Domine et al, 2000;Huthwelker et al, 2001Huthwelker et al, , 2004Cho et al, 2002;Boxe et al, 2003;Khvorostyanov and Curry, 2004;Sadtchenko et al, 2004͒. Particular emphasis is on the uptake of SO 2 , which is a significant component of volcanic emissions and of the combustion of fossil fuels.…”
Section: Ice Core Climate Proxiesmentioning
confidence: 99%